Great tales from English history. [Vol. 1], The truth about King Arthur, Lady Godiva, Richard the Lionheart, and more - Lacey, Robert (Little, Brown, 2004)
There was a time, as recently as nine thousand years ago, when the British Isles were not islands at all. After the bleakness of the successive ice ages, the southeastern corner of modern England was still linked to Europe by a wide swathe of low-lying marshes. People crossed to and fro, and so did animals - including antelopes and brown bears. We know this because the remains of these creatures were discovered by modern archaeologists in a cave in the Cheddar Gorge near Bristol. Scattered among numerous wild horse bones, the scraps of bear and antelope had made up the larder of 'Cheddar Man', England's oldest complete skeleton, found lying nearby in the cave with his legs curled up under him. According to the radiocarbon dating of his bones, Cheddar Man lived and died around 7150 BC. He was a member of one of the small bands of hunter-gatherers who were then padding their way over the soft forest floors of north-western Europe. The dry cave was his home base, where mothers and grandmothers reared children, kindling fires for warmth and lighting and for cooking the family dinner. We don't know what language Cheddar Man spoke. But we can deduce that wild horsemeat was his staple food and that he hunted his prey across the grey-green Mendip Hills with traps, clubs and spears tipped with delicately sharpened leaf-shaped flints.